POTENSI SUMBER DAYA LAHAN DAN OPTIMALISASI PENGEMBANGAN KOMODITAS PENGHASIL I ndonesia memiliki sumber daya lahan yang sangat luas untuk pengembang- an berbagai komoditas pertanian. Luas daratan Indonesia mencapai 188,20 juta ha, yang terdiri atas 148 ju - Anny Mulyani; Irsal Las (Jurnal Penelitian dan Pengembangan Pertanian, 2008)
Land resources potential and optimalization of bioenergy producing commodities development in IndonesiaOne of the current issues in Indonesia is the scarcity of fossil fuel availability in such a way that the alternativerenewable energy sources need to be explored. Various plants have potential as bioenergy, such as oil palm,coconut, maize, cassava, sugar cane, sago palm, and jatropha. The National Team for Bio-Fuel Resources havetargeted the development of 6.50 million ha land for bio-fuel production in 2005-2015 for oil palm, jatropha,sugar cane, and cassava; 1.50 million ha of which is for jatropha. To support the development of those commodities,the biophysical land suitability evaluation has been conducted. The result revealed that there are a substantial landof about 76.40 million ha for oil palm, coconut, maize, cassava, sugar cane, cotton, sago palm, and jatropha, buta large proportion of the lands have been used for agricultural and nonagricultural purposes. One of the problemsin bioenergy development is the land competition for bioenergy and food producing commodities. Intensificationand diversification of the current bioenergy and food producing crops, per se, will not fulfill the national needs,such that extensification is necessary to avoid the negative impacts on the national food security. An overlaybetween land suitability and land use maps of 2000-2004 period revealed that are substantial land areas of about 7million ha for annual crops and 15.30 million ha for perennial crops. The lands are currently under secondaryforest, bushes, imperata grassland and savanna, and those being abandoned. However, the land holdings need to beidentified.Keywords: Land suitability, bioenergy